Analyzing the Conflict Potential of Unauthorized Viralization on Social Media through Galtung’s Conflict Theory - Septiani, Kartika; Uksan, Arifuddin; Yusnaldi; Setiawibawa, Rachmat (Cita konsultindo, 2025)
The phenomenon of making someone go viral without consent on social media has emerged as a pressing social issue, primarily linked to the violation of privacy rights. This study aims to analyze the potential conflicts arising from such practices by applying Johan Galtung’s conflict and violence theory. The research employs a qualitative library research method through the review of relevant literature. Findings reveal that viral content without consent contains complex dimensions of conflict. Based on Galtung’s Conflict Triangle (Contradiction, Attitude, Behavior), conflicts arise from the contradiction between privacy rights and freedom of expression, evolve into attitudes of mutual blame, and manifest in behaviors such as mass online shaming (cyberbullying), doxing, and even legal or social sanctions. Furthermore, the application of Galtung’s violence theory highlights the presence of direct, structural, and cultural violence that reinforce one another. The study concludes that there is an urgent need for specific regulations on digital privacy protection, the promotion of ethical digital literacy, enhanced reporting mechanisms on social media platforms, and psychosocial support services for victims. These measures are expected to foster a safer, fairer, and more humane digital space.